Immune Response in the Common Raccoon (Procyon lotor) to Modified Live Canine Distemper and Feline Panleukopenia Vaccines - Staudenmaier, Anne; Miller, Erica; Dubovi, Joseph (Wildlife Rehabilitation Bulletin, 2014)
The common raccoon, Procyon lotor, while in a separate family from the dog and cat, is susceptible to diseases traditionally associated with these domestic small animals. Thus, the species’ potential for transmitting these devastating diseases back to these small domestic animals should not be ignored. Though vaccinating wild raccoons for canine distemper and feline panleukopenia has been a common practice in wildlife rehabilitation for the past few decades, little is known about the actual efficacy of these vaccines. The purpose of this study was to investigate the antibody titers produced by a commonly used vaccination protocol in wild raccoons for canine distemper and the parvoviruses. Pre‒ and post‒vaccination blood was taken from 49 orphaned raccoons brought to Mercer County Wildlife Center in Titusville, New Jersey, and samples were sent to Cornell University for titer determination. Animals with low pre‒vaccination antibody levels showed appreciable rises in titers for canine distemper. For the parvovirus family, while still protective in most cases, titer rise was much less dramatic, and in two cases, vaccine failure was noted. Raccoons presenting with positive titers pre‒vaccination—most likely due to maternal colostral protection—did not develop a significant immunological response to vaccination if titers were above 1:192, suggesting that colostral antibodies may persist long enough to interfere with current vaccination schedules used by rehabilitation centers and protocols may need to be adjusted to extend for longer time periods.